A ternary positive electrode material with core-shell structure, a preparation method thereof, and a lithium-ion battery

By modifying lithium manganese iron phosphate coating with high nickel content, it forms a core-shell structure, solving the problems of material thermal stability and cycling performance, achieving higher energy density and better battery performance.

CN115692675BActive Publication Date: 2025-02-11EVE POWER CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202211494068.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-25
Publication Date
2025-02-11
Estimated Expiration
2042-11-25

AI Technical Summary

Technical Problem

The thermal stability of the ternary cathode material with high nickel content is low, and Ni4+ ions are easy to react with the electrolyte, resulting in a degradation of battery performance.

Method used

Modified lithium manganese ferrophosphate material is used to coat the high nickel content ternary positive electrode material to form a core-shell structure to improve the thermal stability and cycling performance of the material.

Benefits of technology

Through the modification of the cladding layer, the thermal stability and rate performance of the ternary positive electrode material are improved, side reactions with the electrolyte are avoided, and the overall performance of the battery is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003964844090000131
    Figure BDA0003964844090000131
Patent Text Reader

Abstract

The present invention provides a ternary positive electrode material with a core-shell structure, a preparation method thereof and a lithium ion battery. The ternary positive electrode material with a core-shell structure comprises a ternary positive electrode material core and a coating layer coated on the surface of the ternary positive electrode material core. The structural formula of the ternary positive electrode material is LiNi x Co y Mn 1‑x‑ y O 2 , wherein 0.8≤x<1, 0<y≤0.1; the coating layer comprises a porous modified lithium manganese iron phosphate material, and the structural formula of the porous modified lithium manganese iron phosphate material is LiFe 1‑z‑a Mn z M a PO 4 , M is at least one of Ti, Zr or Al, wherein 0≤z≤0.4, 0.01≤a≤0.05. The present invention uses modified lithium manganese iron phosphate to coat the ternary positive electrode material with a high nickel content, thereby improving the thermal stability and cycle performance of the ternary positive electrode material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode materials, and in particular relates to a ternary positive electrode material with a core-shell structure, a preparation method thereof, and a lithium ion battery. Background Art

[0002] Ternary cathode materials are widely used in various fields due to their high energy density. In recent years, in order to further improve the energy density of ternary cathode materials, researchers have achieved this goal by increasing the nickel content in ternary materials. Currently, the nickel content has gradually been increased to more than 80%. The increase in nickel content has caused the following problems: on the one hand, the thermal stability of ternary cathode materials with high nickel content is low; on the other hand, the cathode materials will produce more Ni 4+ Ion, Ni 4+ The ions have strong oxidizing properties, so they easily react with the electrolyte and undergo irreversible phase changes, thereby causing the performance of the battery to deteriorate.

[0003] In order to improve the above problems, the prior art discloses coating a physical protective layer on the surface of a ternary positive electrode material with a high nickel content, thereby reducing or isolating the contact between the active material and the electrolyte and air, improving the cycle stability of the material, and thus improving the comprehensive performance of the material. For example, CN104733723A discloses a LiCoO 2 The coated modified ternary cathode material is coated with LiCoO 2 The oxide further improves the discharge performance of the ternary material, and its cycle performance under high voltage 4.6V is significantly higher than that of ordinary ternary cathode materials. However, the nickel content in the ternary cathode material in the above technical solution is low, and a higher energy density cannot be obtained.

[0004] Therefore, in the art, there is an urgent need to develop a positive electrode material with a high nickel content, which not only has good structural stability and electrochemical properties, but also does not cause side reactions with the electrolyte. Summary of the invention

[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a ternary positive electrode material with a core-shell structure, a preparation method thereof and a lithium ion battery. The present invention uses modified lithium manganese iron phosphate to coat the ternary positive electrode material with a high nickel content, thereby improving the thermal stability and cycle performance of the ternary positive electrode material.

[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0007] In a first aspect, the present invention provides a ternary positive electrode material with a core-shell structure, wherein the ternary positive electrode material with a core-shell structure comprises a ternary positive electrode material core and a coating layer coated on the surface of the ternary positive electrode material core, and the structural formula of the ternary positive electrode material is LiNi x Co y Mn 1-x-y O 2 , where 0.8≤x<1, 0<y≤0.1;

[0008] The coating layer includes a porous modified lithium manganese iron phosphate material, and the structural formula of the porous modified lithium manganese iron phosphate material is LiFe 1-z-a Mn z M a PO 4 , M is at least one of Ti, Zr or Al elements, wherein 0≤z≤0.4, 0.01≤a≤0.05.

[0009] The present invention uses a modified lithium manganese iron phosphate material to coat a ternary positive electrode material with a high nickel content. First, it can improve the thermal stability of the ternary positive electrode material, prevent the ternary positive electrode material from directly contacting the electrolyte and air, and thus improve the structural stability of the positive electrode material. At the same time, lithium manganese iron phosphate itself has a high energy density, and the ternary positive electrode material will not have a large energy density loss due to the coating step.

[0010] In addition, the present application also doped the lithium manganese iron phosphate with other elements, and the doping caused defects inside the crystal, which were conducive to the diffusion of lithium ions, and the difference in charge valence produced a charge difference, which formed cation vacancies through the charge compensation mechanism, improved the conductivity of the ternary positive electrode material, and further improved the rate performance of the ternary positive electrode material with a core-shell structure. Secondly, the in-situ coating of the modified lithium manganese iron phosphate material consumed the residual lithium on the surface of the ternary positive electrode material, improving its overall performance.

[0011] Finally, compared with the direct coating of the ternary positive electrode material with undoped lithium manganese iron phosphate material, the rate performance of the lithium manganese iron phosphate material is poor, so its coating effect cannot be fully exerted. The present invention further regulates the atomic ratio in the structure of the porous modified lithium manganese iron phosphate material, and the appropriate manganese content makes the modified lithium manganese iron phosphate coating layer material have a higher energy density and better cycle performance (the cycle performance will not be reduced due to the dissolution of manganese), giving full play to the role of the coating layer material.

[0012] In the present invention, the structural formula of the ternary positive electrode material is LiNi x Co y Mn 1-x-y O 2, where 0.8≤x<1, 0<y≤0.1, for example, LiNi 0.8 Co 0.1 Mn 0.1 O 2 、LiNi 0.85 Co 0.05 Mn 0.1 O 2 、LiNi 0.88 Co 0.02 Mn 0.1 O 2 wait.

[0013] In the present invention, the structural formula of the porous modified lithium manganese iron phosphate material is LiFe 1-z-a Mn z M a PO 4 , M is at least one of Ti, Zr or Al, wherein 0≤z≤0.4, 0.01≤a≤0.05, for example, LiFe 0.89 Mn 0.1 Ti 0.01 PO 4 、LiFe 0.83 Mn 0.15 Ti 0.02 PO 4 、LiFe 0.79 Mn 0.2 Ti 0.01 PO 4 、LiFe 0.72 Mn 0.25 Ti 0.03 PO 4 、LiFe 0.67 Mn 0.3 Ti 0.03 PO 4 、LiFe 0.55 Mn 0.4 Ti 0.05 PO 4 、LiFe 0.95 Ti 0.05 PO 4 .

[0014] Preferably, the coating layer also includes organic carbon.

[0015] In the present invention, the raw materials for preparing the organic carbon contained in the coating layer are cracked and oxidized when encountering oxygen during the heat preservation process to produce carbon dioxide and water, forming a loose porous structure. Therefore, the electrolyte can enter the internal pores, which can effectively increase the migration rate of lithium ions, improve the rate performance of the ternary positive electrode material with a core-shell structure, and give full play to its coating effect.

[0016] Preferably, the raw material for preparing the organic carbon includes any one of glucose, sucrose, starch, maltose or polyethylene glycol, or a combination of at least two thereof.

[0017] Preferably, the mass percentage of organic carbon in the coating layer is 15% to 35%, for example, it can be 15%, 18%, 20%, 22%, 25%, 28%, 30%, 32% or 35%.

[0018] Preferably, the mass percentage of the core of the ternary positive electrode material in the ternary positive electrode material with a core-shell structure is 80% to 90%, for example, it can be 80%, 82%, 85%, 88% or 90%.

[0019] In the present invention, by adjusting the mass percentage of the inner core of the ternary positive electrode material, the high compaction density and high specific capacity characteristics of the inner core material are fully utilized to ensure the performance of the positive electrode material. If the content is too low, the specific capacity and energy density of the positive electrode material will be reduced; otherwise, a complete coating layer cannot be formed, reducing the modification and enhancement effect of the coating layer.

[0020] Preferably, the mass percentage of the coating layer in the ternary positive electrode material with a core-shell structure is 10% to 20%, for example, it can be 10%, 12%, 15%, 18% or 20%.

[0021] In the present invention, by adjusting the mass percentage of the coating layer, a complete coating layer is formed on the surface of the core material, and the modification effect of the coating layer is fully exerted. If the content is too low, a complete coating layer cannot be formed due to too little coating layer material, and the coating modification effect is limited; otherwise, the specific capacity and energy density of the positive electrode material will be reduced due to too much coating layer material with low compaction density and low specific capacity.

[0022] In a second aspect, the present invention provides a method for preparing a ternary cathode material having a core-shell structure according to the first aspect, the method comprising the following steps:

[0023] (1) mixing an iron source, an optional manganese source, an M source and a solvent, then adding a ternary positive electrode material, stirring, and adding a phosphorus source to react, filtering and washing after the reaction, and calcining the precipitate to obtain a precursor material;

[0024] (2) The precursor material obtained in step (1) and the lithium source are mixed and spray-dried, and then calcined in stages to obtain the ternary positive electrode material with a core-shell structure.

[0025] Preferably, the iron source in step (1) comprises any one of ferrous sulfate, ferrous chloride, ferric nitrate or ferrous oxalate, or a combination of at least two thereof.

[0026] Preferably, the manganese source in step (1) comprises any one of manganous sulfate, manganese chloride or manganese nitrate, or a combination of at least two thereof.

[0027] Preferably, the M source in step (1) includes any one or a combination of at least two of titanium sulfate, titanium chloride, titanium nitrate, zirconium sulfate, zirconium chloride, zirconium nitrate, aluminum sulfate, aluminum chloride or aluminum nitrate.

[0028] Preferably, the solvent in step (1) is deionized water.

[0029] Preferably, the structural formula of the ternary cathode material in step (1) is LiNi x Co y Mn 1-x-y O 2 , where 0.8≤x<1, 0<y≤0.1.

[0030] Preferably, the phosphorus source in step (1) comprises ammonium phosphate and / or diammonium phosphate.

[0031] Preferably, the step (1) further comprises adding an organic carbon source before the reaction.

[0032] Preferably, the organic carbon source comprises any one of glucose, sucrose, starch, maltose or polyethylene glycol, or a combination of at least two thereof.

[0033] Preferably, the reaction temperature in step (1) is 20-50°C, for example, 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C; and the reaction time is 3-8h, for example, 3h, 4h, 5h, 6h, 7h, 8h.

[0034] Preferably, the step (1) further includes vacuum drying before calcination.

[0035] Preferably, the temperature of the vacuum drying treatment is 80-100°C, for example, 80°C, 85°C, 90°C, 95°C, 100°C; the time is 20-30h, for example, 20h, 22h, 25h, 28h, 30h.

[0036] Preferably, the calcination temperature in step (1) is 500-750°C, for example, 500°C, 550°C, 600°C, 650°C, 700°C, 750°C; and the calcination time is 2-5h, for example, 2h, 3h, 4h, 5h.

[0037] Preferably, the lithium source in step (2) comprises lithium hydroxide and / or lithium carbonate.

[0038] Preferably, the spray drying temperature in step (2) is 120-200°C, for example, 120°C, 150°C, 180°C, 200°C; the pressure is 7-15MPa, for example, 7MPa, 9MPa, 12MPa, 14MPa, 15MPa.

[0039] Preferably, the staged calcination in step (2) includes, in sequence, first sintering at 200-300°C (for example, 200°C, 220°C, 250°C, 280°C, 300°C) for 3-5h (for example, 3h, 3.5h, 4h, 4.5h, 5h), and then sintering at 600-800°C (for example, 600°C, 620°C, 650°C, 680°C, 700°C, 720°C, 750°C, 780°C, 800°C) for 8-15h (for example, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h).

[0040] In a third aspect, the present invention provides a lithium-ion battery, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises the ternary positive electrode material with a core-shell structure according to the first aspect.

[0041] Compared with the prior art, the present invention has the following beneficial effects:

[0042] The present invention provides a ternary positive electrode material with a core-shell structure, which uses a modified lithium iron manganese phosphate material to coat a ternary positive electrode material with a high nickel content. First, it can improve the thermal stability of the ternary positive electrode material, prevent the ternary positive electrode material from directly contacting the electrolyte and the air, and thus improve the structural stability of the positive electrode material. At the same time, lithium iron manganese phosphate itself has a high energy density, and the ternary positive electrode material will not have a large energy density loss due to the coating step.

[0043] In addition, the present application also doped the lithium manganese iron phosphate with other elements, and the doping caused defects inside the crystal, which were conducive to the diffusion of lithium ions, and the difference in charge valence produced a charge difference, which formed cation vacancies through the charge compensation mechanism, improved the conductivity of the ternary positive electrode material, and further improved the rate performance of the ternary positive electrode material with a core-shell structure. Secondly, the in-situ coating of the modified lithium manganese iron phosphate material consumed the residual lithium on the surface of the ternary positive electrode material, improving its overall performance. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] Example 1

[0046] This embodiment provides a ternary positive electrode material with a core-shell structure. The ternary positive electrode material with a core-shell structure includes LiNi 0.8 Co 0.1 Mn 0.1 O 2 The core of the ternary cathode material and the coating on LiNi 0.8 Co 0.1 Mn 0.1 O 2 The coating layer on the surface of the core of the ternary positive electrode material includes LiFe 0.72 Mn 0.25 Ti 0.03 PO 4 Porous modified lithium manganese iron phosphate materials and organic carbon.

[0047] LiNi in ternary cathode materials with core-shell structure 0.8 Co 0.1 Mn 0.1 O 2 The mass percentage of the inner core of the ternary positive electrode material is 85%, the mass percentage of the coating layer is 15%, and the mass percentage of organic carbon in the coating layer is 25%.

[0048] This embodiment also provides a method for preparing the above-mentioned ternary positive electrode material with a core-shell structure, which comprises the following steps:

[0049] (1) Mix ferrous sulfate, manganese sulfate, titanium sulfate and deionized water, and then add LiNi 0.8 Co 0.1 Mn 0.1 O 2 The ternary positive electrode material is stirred to form a suspension, and ammonium phosphate and glucose are added to react at 35°C for 5 hours. After the reaction, the suspension is filtered and washed until the pH of the washing water is neutral. The precipitate is placed at 90°C for vacuum drying for 25 hours, and then the dried precipitate is calcined at 650°C for 3.5 hours to obtain a precursor material.

[0050] (2) The precursor material obtained in step (1) and lithium hydroxide are mixed, ground and spray-dried, wherein the spray drying temperature is 150° C. and the pressure is 12 MPa, and the mixture is first sintered at 250° C. for 4 h and then sintered at 700° C. for 11 h to obtain a ternary positive electrode material with a core-shell structure.

[0051] Example 2

[0052] This embodiment provides a ternary positive electrode material with a core-shell structure. The ternary positive electrode material with a core-shell structure includes LiNi 0.8 Co 0.1 Mn0.1 O 2 The core of the ternary cathode material and the coating on LiNi 0.8 Co 0.1 Mn 0.1 O 2 The coating layer on the surface of the core of the ternary positive electrode material includes LiFe 0.72 Mn 0.25 Ti 0.03 PO 4 Porous modified lithium manganese iron phosphate materials and organic carbon.

[0053] LiNi in ternary cathode materials with core-shell structure 0.8 Co 0.1 Mn 0.1 O 2 The mass percentage of the inner core of the ternary positive electrode material is 82%, the mass percentage of the coating layer is 18%, and the mass percentage of organic carbon in the coating layer is 20%.

[0054] This embodiment also provides a method for preparing the above-mentioned ternary positive electrode material with a core-shell structure, which comprises the following steps:

[0055] (1) Mix ferrous sulfate, manganese sulfate, titanium sulfate and deionized water, and then add LiNi 0.8 Co 0.1 Mn 0.1 O 2 The ternary positive electrode material is stirred to form a suspension, and ammonium phosphate and glucose are added to react at 35°C for 5 hours. After the reaction, the suspension is filtered and washed until the pH of the washing water is neutral. The precipitate is placed at 90°C for vacuum drying for 25 hours, and then the dried precipitate is calcined at 650°C for 3.5 hours to obtain a precursor material.

[0056] (2) The precursor material obtained in step (1) and lithium hydroxide are mixed, ground and spray-dried, wherein the spray drying temperature is 160° C. and the pressure is 10 MPa, and the mixture is first sintered at 250° C. for 4 h and then sintered at 700° C. for 11 h to obtain a ternary positive electrode material with a core-shell structure.

[0057] Example 3

[0058] This embodiment provides a ternary positive electrode material with a core-shell structure. The ternary positive electrode material with a core-shell structure includes LiNi 0.8 Co 0.1 Mn 0.1 O 2 The core of the ternary cathode material and the coating on LiNi 0.8 Co 0.1 Mn 0.1O 2 The coating layer on the surface of the core of the ternary positive electrode material includes LiFe 0.72 Mn 0.25 Ti 0.03 PO 4 Porous modified lithium manganese iron phosphate materials and organic carbon.

[0059] LiNi in ternary cathode materials with core-shell structure 0.8 Co 0.1 Mn 0.1 O 2 The mass percentage of the inner core of the ternary positive electrode material is 87%, the mass percentage of the coating layer is 13%, and the mass percentage of organic carbon in the coating layer is 30%.

[0060] This embodiment also provides a method for preparing the above-mentioned ternary positive electrode material with a core-shell structure, which comprises the following steps:

[0061] (1) Mix ferrous sulfate, manganese sulfate, titanium sulfate and deionized water, and then add LiNi 0.8 Co 0.1 Mn 0.1 O 2 The ternary positive electrode material is stirred to form a suspension, and ammonium phosphate and glucose are added to react at 35°C for 5 hours. After the reaction, the suspension is filtered and washed until the pH of the washing water is neutral. The precipitate is placed at 90°C for vacuum drying for 25 hours, and then the dried precipitate is calcined at 650°C for 3.5 hours to obtain a precursor material.

[0062] (2) The precursor material obtained in step (1) and lithium hydroxide are mixed, ground and spray-dried, wherein the spray-drying temperature is 170° C. and the pressure is 9 MPa, and the mixture is first sintered at 250° C. for 4 h and then sintered at 700° C. for 11 h to obtain a ternary positive electrode material with a core-shell structure.

[0063] Example 4

[0064] This embodiment provides a ternary positive electrode material with a core-shell structure. The ternary positive electrode material with a core-shell structure includes LiNi 0.8 Co 0.1 Mn 0.1 O 2 The core of the ternary cathode material and the coating on LiNi 0.8 Co 0.1 Mn 0.1 O 2 The coating layer on the surface of the core of the ternary positive electrode material includes LiFe 0.99 Al 0.01 PO 4Porous modified lithium manganese iron phosphate materials and organic carbon.

[0065] LiNi in ternary cathode materials with core-shell structure 0.8 Co 0.1 Mn 0.1 O 2 The mass percentage of the inner core of the ternary positive electrode material is 80%, the mass percentage of the coating layer is 20%, and the mass percentage of the organic carbon in the coating layer is 15%.

[0066] This embodiment also provides a method for preparing the above-mentioned ternary positive electrode material with a core-shell structure, which comprises the following steps:

[0067] (1) Mix ferrous sulfate, aluminum sulfate and deionized water, and then add LiNi 0.8 Co 0.1 Mn 0.1 O 2 The ternary cathode material is stirred to form a suspension, and diammonium phosphate and sucrose are added to react at 20°C for 8 hours. After the reaction, the suspension is filtered and washed until the pH of the washing water is neutral. The precipitate is placed at 80°C for vacuum drying for 30 hours, and then the dried precipitate is calcined at 500°C for 5 hours to obtain a precursor material.

[0068] (2) The precursor material obtained in step (1) and lithium carbonate are mixed, ground and spray-dried, wherein the spray drying temperature is 120° C. and the pressure is 15 MPa, and the mixture is first sintered at 200° C. for 5 h and then sintered at 600° C. for 15 h to obtain a ternary positive electrode material with a core-shell structure.

[0069] Example 5

[0070] This embodiment provides a ternary positive electrode material with a core-shell structure. The ternary positive electrode material with a core-shell structure includes LiNi 0.8 Co 0.1 Mn 0.1 O 2 The core of the ternary cathode material and the coating on LiNi 0.8 Co 0.1 Mn 0.1 O 2 The coating layer on the surface of the core of the ternary positive electrode material includes LiFe 0.55 Mn 0.4 Al 0.05 PO 4 Porous modified lithium manganese iron phosphate materials and organic carbon.

[0071] LiNi in ternary cathode materials with core-shell structure 0.8 Co 0.1 Mn0.1 O 2 The mass percentage of the inner core of the ternary positive electrode material is 90%, the mass percentage of the coating layer is 10%, and the mass percentage of organic carbon in the coating layer is 35%.

[0072] This embodiment also provides a method for preparing the above-mentioned ternary positive electrode material with a core-shell structure, which comprises the following steps:

[0073] (1) Mix ferrous sulfate, manganese sulfate, aluminum sulfate and deionized water, and then add LiNi 0.8 Co 0.1 Mn 0.1 O 2 The ternary positive electrode material is stirred to form a suspension, and diammonium phosphate and sucrose are added while stirring to react at 50°C for 3 hours. After the reaction is completed, it is filtered and washed until the pH of the washing water is neutral, and the precipitate is placed at 100°C for vacuum drying for 20 hours, and then the dried precipitate is calcined at 750°C for 2 hours to obtain a precursor material;

[0074] (2) The precursor material obtained in step (1) and lithium carbonate are mixed, ground and spray-dried, wherein the spray drying temperature is 200° C. and the pressure is 7 MPa, and the mixture is first sintered at 300° C. for 3 h and then sintered at 800° C. for 8 h to obtain a ternary positive electrode material with a core-shell structure.

[0075] Example 6

[0076] The difference between this embodiment and embodiment 1 is that the structural formula of the porous modified lithium manganese iron phosphate material is LiFe 0.37 Mn 0.6 Ti 0.03 PO 4 , the rest are the same as in Example 1.

[0077] Example 7

[0078] The difference between this embodiment and embodiment 1 is that the structural formula of the porous modified lithium manganese iron phosphate material is LiFe 0.6 Mn 0.25 Ti 0.15 PO 4 , the rest are the same as in Example 1.

[0079] Example 8

[0080] The difference between this embodiment and embodiment 1 is that the mass percentage of the core of the ternary positive electrode material in the core-shell structure is 95%, and the mass percentage of the coating layer in the core-shell structure is 5%, and the rest is the same as embodiment 1.

[0081] Example 9

[0082] The difference between this embodiment and embodiment 1 is that the mass percentage of the core of the ternary positive electrode material in the core-shell structure is 75%, and the mass percentage of the coating layer in the core-shell structure is 25%, and the rest is the same as embodiment 1.

[0083] Example 10

[0084] The difference between this embodiment and embodiment 1 is that the mass percentage of organic carbon in the coating layer is 10%, and the rest is the same as embodiment 1.

[0085] Embodiment 11

[0086] The difference between this embodiment and embodiment 1 is that the mass percentage of organic carbon in the coating layer is 40%, and the rest is the same as embodiment 1.

[0087] Comparative Example 1

[0088] The difference between this comparative example and Example 1 is that the coating layer is replaced by a carbon layer, and the rest is the same as Example 1.

[0089] Comparative Example 2

[0090] The difference between this comparative example and Example 1 is that LiFe 0.72 Mn 0.25 Ti 0.03 PO 4 The porous modified lithium manganese iron phosphate material is replaced by an unmodified lithium manganese iron phosphate material, and the rest is the same as in Example 1.

[0091] Comparative Example 3

[0092] The difference between this comparative example and Example 1 is that LiFe 0.72 Mn 0.25 Ti 0.03 PO 4 The porous modified lithium manganese iron phosphate material is replaced by a Mg-modified lithium manganese iron phosphate material, and the rest is the same as in Example 1.

[0093] Application Examples 1 to 11 and Comparative Application Examples 1 to 3

[0094] The ternary positive electrode materials with core-shell structure provided in Examples 1 to 11 and Comparative Examples 1 to 3 are used to prepare lithium-ion batteries, and the preparation method is as follows:

[0095] Preparation of positive electrode sheet: After the above-mentioned ternary positive electrode material with core-shell structure, conductive carbon black and polyvinylidene fluoride are fully stirred in a mass ratio of 90:5:5, N-methylpyrrolidone is added to obtain positive electrode slurry, the prepared slurry is coated on aluminum foil, cold pressed, baked and die-cut into strips to prepare positive electrode sheets;

[0096] Preparation of negative electrode sheet: After fully stirring the negative electrode active material graphite, conductive carbon black and sodium carboxymethyl cellulose in a mass ratio of 92:4:4, deionized water is added to obtain negative electrode slurry, the prepared slurry is coated on copper foil, cold pressed, baked and die-cut into strips to prepare negative electrode sheets;

[0097] Preparation of electrolyte: Using 1 mol LiPF 6 As the lithium salt, the solvent was a mixed solvent consisting of EC / DC / EMC (volume ratio of 1:1:1).

[0098] Preparation of lithium-ion batteries: The positive electrode sheet, polypropylene separator and negative electrode sheet are wound into a core with a certain pressure, and the prepared core is placed in an aluminum shell. Under negative pressure conditions, the electrolyte is injected into the battery cell. After sufficient rest, subsequent processes such as packaging, formation and capacity division are carried out to obtain a lithium-ion battery.

[0099] Test conditions

[0100] The lithium-ion batteries prepared in Application Examples 1 to 11 and Comparative Application Examples 1 to 3 were subjected to performance tests respectively, and the test methods are as follows:

[0101] Rate performance: The lithium secondary battery was charged at 1C under constant current conditions at 25°C until 4.2V / 0.05C, and then discharged at 3C under constant current (CC) conditions to 2.8V, and the discharge specific capacity was calculated;

[0102] Cycle performance: The lithium secondary battery was charged at 1C under constant current conditions at 25°C until 4.2V / 0.05C, and then discharged at 1C under constant current (CC) conditions to 2.8V. This was considered as one cycle, and the test was repeated for 1000 cycles. The capacity retention rate of the 1000th cycle during the charge and discharge process was measured.

[0103] The test results are shown in Table 1:

[0104] Table 1

[0105]

[0106] It can be seen from the data in Table 1 that Examples 1-5 provided by the present invention show that the ternary cathode material with a core-shell structure has good rate performance and cycle life.

[0107] Example 6 is a case where the parameter z of the porous modified lithium manganese iron phosphate material is too high. If the manganese content is too high, it will cause its dissolution, reducing the cycle performance of the battery; Example 7 is a case where the parameter a of the porous modified lithium manganese iron phosphate material is too high. If the content of doped elements is too high, the content of active elements will be reduced, reducing the specific capacity and energy density of the positive electrode material; Examples 8-9 show that the material can be fully coated while ensuring a high specific capacity; Examples 10-11 show that the content of organic carbon is regulated to make the material have high conductivity;

[0108] Comparative Example 1 is the case of replacing the coating layer. The ordinary carbon coating layer cannot improve the energy density of the positive electrode material; Comparative Example 2 is the case of unmodified lithium manganese iron phosphate material, and Comparative Example 3 is the case of replacing the Mg element to modify the lithium manganese iron phosphate material, which cannot achieve the ideal technical effect of the present invention.

[0109] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A ternary cathode material with a core-shell structure, characterized in that: The ternary positive electrode material with a core-shell structure comprises a ternary positive electrode material core and a coating layer coated on the surface of the ternary positive electrode material core. The structural formula of the ternary positive electrode material is LiNi x Co y Mn 1-x-y O2, where 0.8≤x<1, 0<y≤0.1; The coating layer includes a porous modified lithium manganese iron phosphate material, and the structural formula of the porous modified lithium manganese iron phosphate material is LiFe 1-z-a Mn z M a PO4, M is at least one of Ti, Zr or Al, wherein 0<z≤0.4, 0.01≤a≤0.05; The mass percentage of the core of the ternary positive electrode material in the ternary positive electrode material with a core-shell structure is 80% to 90%; The mass percentage of the coating layer in the ternary positive electrode material with a core-shell structure is 10% to 20%.

2. The ternary cathode material with a core-shell structure according to claim 1, characterized in that: The coating layer also includes organic carbon.

3. The ternary cathode material with a core-shell structure according to claim 2, characterized in that: The raw material for preparing the organic carbon includes any one of glucose, sucrose, starch, maltose or polyethylene glycol, or a combination of at least two of them.

4. The ternary cathode material with a core-shell structure according to claim 2, characterized in that: The mass percentage of organic carbon in the coating layer is 15% to 35%.

5. A method for preparing a ternary cathode material having a core-shell structure according to any one of claims 1 to 4, characterized in that: The method comprises the following steps: (1) Mixing an iron source, a manganese source, an M source and a solvent, then adding a ternary positive electrode material, stirring, and adding a phosphorus source for reaction. After the reaction is completed, filtering and washing are performed, and the precipitate is calcined to obtain a precursor material; (2) The precursor material obtained in step (1) and the lithium source are mixed and spray-dried, and then calcined in stages to obtain the ternary positive electrode material with a core-shell structure.

6. The method according to claim 5, characterized in that The iron source in step (1) includes any one of ferrous sulfate, ferrous chloride, ferric nitrate or ferrous oxalate, or a combination of at least two thereof.

7. The method according to claim 5, characterized in that The manganese source in step (1) includes any one of manganous sulfate, manganese chloride or manganese nitrate, or a combination of at least two of them.

8. The method according to claim 5, characterized in that The M source in step (1) includes any one of titanium sulfate, titanium chloride, titanium nitrate, zirconium sulfate, zirconium chloride, zirconium nitrate, aluminum sulfate, aluminum chloride or aluminum nitrate, or a combination of at least two thereof.

9. The method according to claim 5, characterized in that The solvent in step (1) is deionized water.

10. The method according to claim 5, characterized in that The structural formula of the ternary positive electrode material in step (1) is LiNi x Co y Mn 1-x-y O2, where 0.8≤x<1, 0<y≤0.

1.

11. The method according to claim 5, characterized in that The phosphorus source in step (1) includes ammonium phosphate and / or diammonium phosphate.

12. The method according to claim 5, characterized in that The step (1) further comprises adding an organic carbon source before the reaction.

13. The method according to claim 12, characterized in that The organic carbon source includes any one of glucose, sucrose, starch, maltose or polyethylene glycol, or a combination of at least two of them.

14. The method according to claim 5, characterized in that The reaction temperature in step (1) is 20-50°C and the reaction time is 3-8h.

15. The method according to claim 5, characterized in that The step (1) also includes vacuum drying before calcination.

16. The method according to claim 15, characterized in that The vacuum drying process is carried out at a temperature of 80-100° C. and for a time of 20-30 hours.

17. The method according to claim 5, characterized in that The calcination temperature in step (1) is 500-750°C and the calcination time is 2-5 hours.

18. The method according to claim 5, characterized in that The lithium source in step (2) includes lithium hydroxide and / or lithium carbonate.

19. The method according to claim 5, characterized in that The spray drying temperature in step (2) is 120-200° C. and the pressure is 7-15 MPa.

20. The method according to claim 5, characterized in that The staged calcination in step (2) includes first sintering at 200-300°C for 3-5 hours, and then sintering at 600-800°C for 8-15 hours.

21. A lithium ion battery, characterized in that: The lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a ternary positive electrode material with a core-shell structure according to any one of claims 1 to 4.

Citation Information

Patent Citations

  • Preparation method for LiCoO2-coated modified ternary cathode material

    CN104733723A

  • A lithium ion battery composite cathode material and a preparation method thereof

    CN109273684A

  • Lithium manganese iron phosphate positive electrode material as well as preparation method and application thereof

    CN115020685A